Evaluation of Cell-detaching Effect of EDTA in Combination with Oxaliplatin for a Possible Application in HIPEC After Cytoreductive Surgery: A Preliminary in-vitro Study - Schubert, Justyna; Khosrawipour, Tanja; Pigazzi, Alessio; Kulas, Joanna; Bania, Jacek; Migdal, Pawel; Arafkas, Mohamed; Khosrawipour, Veria (Current Pharmaceutical Design, 2019)
Background: Ethylenediaminetetraacetic acid (EDTA), a commonly used compound in laboratory medicine, is known for its membrane-destabilization capacity and cell-detaching effect. This preliminary study aims to assess the potential of EDTA in removing residual tumor cell clusters. Using an in-vitro model, this effect is then compared to the cytotoxic effect of oxaliplatin which is routinely administered during HIPEC procedures. The overall cell toxicity and cell detaching effects of EDTA are compared to those of Oxaliplatin and the additive effect is quantified. Methods: HT-29 (ATCC® HTB-38™) cells were treated with A) EDTA only B) Oxaliplatin only and C) both agents using an in-vitro model. Cytotoxicity and cell detachment following EDTA application were measured via colorimetric MTS assay. Additionally, detached cell groups were visualized using light microscopy and further analyzed by means of electron microscopy. Results: When solely applied, EDTA does not exhibit any cell toxicity nor does it add any toxicity to oxaliplatin. However, EDTA enhances the detachment of adherent colon carcinoma cells by removing up to 65% (p<0.05) of the total initial cell amount. In comparison, the sole application of highly concentrated oxaliplatin induced cell mortality by up to 66% (p<0.05). While detached cells showed no mortality after EDTA treatment, cell clusters exhibited a decreased amount of extracellular and adhesive matrix in-between cells. When combined, Oxaliplatin and EDTA display a significant additive effect with only 30% (mean p <0.01) of residual vitality detected in the initial well. EDTA and Oxaliplatin remove up to 81% (p <0.01) of adhesive HT-29 cells from the surface either by cytotoxic effects or cell detachment. Conclusion: Our data support EDTA’s potential to remove microscopical tumor cell clusters from the peritoneum and possibly act as a supplementary agent in HIPEC procedures with chemotherapy. While adding EDTA to HIPEC procedures may significantly decrease the risk of PM recurrence, further in-vivo and clinical trials are required to evaluate this effect.
Keywords: cytoreductive surgery